Morphometric Changes of the Lumbar Intervertebral Foramen after Percutaneous Endoscopic Foraminoplasty under Local Anesthesia - Henmi, Tatsuhiko; Terai, Tomoya; Nagamachi, Akihiro; Sairyo, Koichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Percutaneous endoscopic diskectomy (PED) for the lumbar spine is a relatively new technique that is becoming more common due to its relatively less invasive nature. However, one possible serious complication is an exiting nerve injury when the cannula of the endoscope is inserted into the neural canal through the intervertebral foramen. A technique to enlarge the intervertebral foramen, called foraminoplasty, was recently established to insert the cannula safely into an appropriate position in the neural canal.Methods In this study we performed foraminoplasty during PED under local anesthesia on 15 patients. Using computed tomography scans before and after surgery, the morphometric changes of the intervertebral foramen were evaluated. Surgery-related complications were reviewed.Results There were 13 men and 2 women, 21 to 86 years of age (mean: 47.1 years). Disk levels were 13 cases at L4–L5, one case at L3–L4, and one case at L5–S1. In 50% of the cases, the mean foraminal area significantly increased from 58.6 mm2 before surgery to 88.4 mm2 after surgery (p < 0.05 by paired t test). The diameter of the foramen was increased at all three points: the lower end plate of the superior vertebrae, the disk, and the upper end plate of the inferior vertebrae. The area increased ∼ 1.5 times, especially at the upper end plate of the inferior vertebrae. In all cases, no exiting nerve injury was encountered during PED.Conclusion Foraminoplasty was an effective method for avoiding exiting nerve root injury during transforaminal PED.
Keywords: foraminoplasty; percutaneous endoscopic diskectomy; local anesthesia; morphology